The friends of Eddie Coyle - Higgins, George V., 1939-1999 (Picador ; Melia [distributor], 2010)
Eddie Coyle is a small-time gun dealer with a big-time problem: who to sell out to avoid going to prison. While mob bosses, cops, hoods, gunmen, thieves, and executioners give Eddie plenty of choices, he has few options. Any decision could cost him his life.